HLA-G 14 bp In/Del and +3142 C/G genotypes are differentially expressed between patients with grade IV gliomas and controls. (3rd April 2021) - de Magalhães, Kênia Cristina S.F.; Silva, Karla R.; Gomes, Nathália A.; Sadissou, Ibrahim; Carvalho, Gérvasio T.; Buzellin, Marcelo A.; Tafuri, Luciene S.; Nunes, Cristiana B.; Nunes, Maurício B.; Donadi, Eduardo A.; da Silva, Istéfani Luciene; Simões, Renata T.
Abstract: Aim: Human Leukocyte Antigen-G (HLA-G) is a non-classical class I molecule that is involved in maternal–fetal immunotolerance. In cancer, this molecule contributes to the tumor escape. The aim of this study was to evaluate the 14 bp In/Del and +3142  C > G polymorphisms of the HLA-G 3′ UTR and its relation with plasma and tissue HLA-G expression in patients with grade IV (high-grade) and grade I/II (low-grade) gliomas and controls. Patients and methods: Peripheral blood and tumor biopsies were collected from 85 patients with gliomas and blood samples from 94 controls. Polymorphisms were analyzed from blood DNA. Soluble HLA-G (sHLA-G) was measured by ELISA in plasma of the subjects and the tissue expression by immunohistochemistry on patient's tissue. Results: Higher levels of sHLA-G were observed in grade IV gliomas patients than in controls ( p  < 0.0001). In grade IV patients, the heterozygous 14pb In/Del, +3142  C/G genotypes and Del/C*In/G haplotype were associated with higher sHLA-G levels ( p  < 0.0001) when compared with controls. GBM patients were stratified into high and low sHLA-G expression and an association was found between +3142  C allele and high sHLA-G plasmatic levels ( p  = 0.0095). Tissue HLA-G immunolabel was higher in high-grade than low-grade gliomas ( p  = 0.0033). Conclusion: This was the first study evaluating HLA-G 3′ UTR polymorphisms and expression in patients with gliomas. The 14 bp In/Del and +3142  C/G genotypes and haplotypes showed high influence over sHLA-G expression, suggesting a heterozygous advantage in the tumor context and may contribute to a worse prognosis in glioma patients.